Discrimination against the obese and very thin students in Brazilian schools - Luis Claudio Kubota (Institute for Applied Economic Research (ipea), 2015)
PeNSE 2012 is a survey conducted by the Brazilian Institute of Geography and Statistics (IBGE), in partnership with the Ministry of Health. PeNSE covers a broad range of subjects, especially risk behavior. This article has the aim of analyzing discrimination against obese and very thin students using PeNSE microdata. Data indicate that students that classify themselves as "very fat" or "very thin" are much more prone to risk behaviors like consumption of illicit drugs, alcohol, cigarettes and laxatives (or vomit inducing), when compared to "normal" pupils. They are also much more likely to suffer from frequent bullying (FB), especially that motivated by their body appearance, to be active bullies, to feel frequently lonely, to suffer from insomnia, family violence, aggressions and injuries. A great percentage was involved in fights and feel that their parents rarely or never understand their problems and preoccupations. Econometric model shows that non "normal" students have a greater chance of suffering FB than "normal" pupils. Male students have greater chance of being frequently discriminated when compared to the female ones. There is no statistical difference between public and private schools. Black, yellow and Indian students have greater chance of suffering FB than white pupils. Students whose mothers didn't study have greater chance of suffering FB than those whose mothers have completed high school education.
Keywords: I18; J12; 330; obesity; thinness; discrimination; bullying; students